2013
DOI: 10.1021/mp4003255
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cationic Phosphorus Dendrimer Toxicity against Murine Neural Cell Lines

Abstract: The purpose of this manuscript is to study the toxic responses against murine embryonic hippocampal cells (mHippoE-18) and neuroblastoma cells (N2a) to treatment with cationic phosphorus dendrimers (CPD). Two low generations of CPD--generation 2 (G2) and generation 3 (G3)--were applied to cell cultures to monitor events leading to either apoptosis or necrosis. These processes were analyzed using several bioassays, which included the detection of reactive oxygen species (ROS), mitochondrial membrane potential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 82 publications
3
37
0
Order By: Relevance
“…The mechanisms of dendrimers' action differ in their nature: carbosilane dendrimers can induce cell apoptosis Weber et al, 2008;Wrobel et al, 2014;Serramía et al, 2015), PAMAM dendrimers -apoptosis (Mukherjee et al, 2010a,b, b;Mukherjee and Byrne, 2013) and autophagy Wang et al, 2014), while phosphorus dendrimers -necrosis (Lazniewska et al, 2013). Thus, our data suggest that inducing several mechanisms of programmed cell death is more effective in cancer treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The mechanisms of dendrimers' action differ in their nature: carbosilane dendrimers can induce cell apoptosis Weber et al, 2008;Wrobel et al, 2014;Serramía et al, 2015), PAMAM dendrimers -apoptosis (Mukherjee et al, 2010a,b, b;Mukherjee and Byrne, 2013) and autophagy Wang et al, 2014), while phosphorus dendrimers -necrosis (Lazniewska et al, 2013). Thus, our data suggest that inducing several mechanisms of programmed cell death is more effective in cancer treatment.…”
Section: Discussionmentioning
confidence: 73%
“…PAMAM dendrimers can induce apoptotic cell death (Mukherjee and Byrne, 2013), whereas CPD leads to necrosis (Lazniewska et al, 2013). Therefore, when used in higher concentration (250 nmol/l siRNAs), the cytotoxicity could be, to some extent, caused by dendrimers, especially in the case of the highly toxic CPD.…”
Section: Discussionmentioning
confidence: 99%
“…As Lazniewska et al [21] reported, the treatment of murine neural cells by these dendrimers at concentrations above 1 µM was followed by a dramatic decrease in cell viability. After investigation of cell death-related processes, authors concluded that CPD treatment leads to necrotic cell death and proposed to improve biomedical potential of dendrimers by the modification of CPD surface with chemical groups lowering their cytotoxicity.…”
Section: Introductionmentioning
confidence: 69%
“…The mHippoE-14 hippocampal cell line is known to possess the characteristics of embryonic hippocampal neurons and enables accurate in vitro assays for use in the discovery, development, and validation of new therapeutics targeted to central nervous system diseases and disorders, including obesity, stress, reproduction, and metabolic disorders (Gingerich et al, 2010; Lazniewska et al, 2013; Evans et al, 2016). Long-term treatment with PIO has been previously reported to influence hippocampal function (Blalock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%